Learning to Plan–and Planning to Learn - Michael, Donald N. (Miles River Press, 1997)
Don Michael says that, yes, the world can meet future social and organ izational challenges - but only if we learn to plan in order– to live uncertainty– to learn from mistakes, actually embrace error– to do goa l setting that is future-responsive– to lower barriers by spanning bou ndaries– to improve personal interaction– to overcome resistance to le arning and change.This book treats planning as the way for persons, or ganizations, and societies to learn their way into the future. It reve als the complex and unavoidable social psychological resistances to le arning that must be overcome by competent citizenry in order to plan f or the future. A viable ecology, Third World development, new-city bui lding, democratic government in a turbulent society – all depend on th e anticipation of future conditions and on planning to meet these cond itions.
Keywords: Social science